Translation and adaptation of parental-child attachment scale in Bangla - Uddin, Abu Zafar Md Riaz; Kawser, Umme; Jony, Rajon Das; Huque, Akib Ul (Dhaka University Journal of Biological Sciences, 2017)
Hudson’s parental‐child attachment scale (PCAS) is a popular instrument to assess the quality of parental child attachment ‐ the emotional bond that influences the social and emotional development of a child. The present study adapted this scale for using with Bangla speaking parents and their children. This study was conducted with 100 children and their parents (either father or mother). The internal consistency of the parental‐child attachment scale was computed by Cronbach’s alpha which was 0.888 for youth items and 0.816 for parent items. The split‐half reliability co‐efficient of the scale was 0.787 for youth items and 0.779 for parent items. So the preliminary reliability and content validity of the scale has been established. Dhaka Univ. J. Biol. Sci. 26(2): 117-123, 2017 (July)